La depresión post parto y su influencia en la conducta de la lactancia materna de mujeres primíparas atendidas en el Centro de Salud Roberto Astudillo, Milagro. Noviembre 2023- abril 2024. - Alarcón Izurieta, Genesis Yaritza (2024)
Postpartum depression is currently a public health problem worldwide, primarily affecting primiparous mothers, who are more likely to discontinue breastfeeding. The primary objective being to analyze the influence of postpartum depression on breastfeeding in primiparous women treated at the Roberto Astudillo health center, it was carried out through an analytical methodological design study, quantitative modality, and a type of cross-sectional research. The study population consisted of 180 primiparous women and the technique of reviewing medical records was used, data collection through the Edinburgh scale that helped identify mothers with PPD, and a survey to determine the influence of PPD on the Breastfeeding. The results showed that 68% of primiparous mothers have postpartum depression, none of whom breastfeed exclusively and only 10% of mothers feed their baby on demand. Concluding that PPD has a negative influence on breastfeeding of primiparous women at the Roberto Astudillo health center.